Assessment of multidimensional self-concept in the area of physical education: validation of a scale - Galán-Arroyo, Carmen; Gomez-Paniagua, Santiago; Castillo-Paredes, Antonio; Rojo-Ramos, Jorge (Frontiers in Sports and Active Living, 2024)
Self-concept is a person's perception of him/herself and how he/she performs in different situations. This aspect must be developed during the formative stages and Physical Education is a fundamental area due to its enormous methodological possibilities. Therefore, the aim of this study is to evaluate the factor structure and reliability of an instrument that allows to analyze the multidimensional selfconcept of high school students in the context of Physical Education. The sample consisted of 1,155 secondary school students from public schools in the Autonomous Community of Extremadura, Spain. After the exploratory and confirmatory analyses, a structure composed of 30 items divided into 5 factors was proposed. This design showed excellent goodness-of-fit indices as well as good internal reliability indicators (Cronbach's Alpha = 0.76-0.88). Therefore, this scale can be considered as a tool to assess the self-concept of high school students in a quick and easy way.